A time-course study of gene expression and antibody repertoire at early time post vaccination of Atlantic salmon. (February 2019) - Lund, Hege; Bakke, Anne Flore; Sommerset, Ingunn; Afanasyev, Sergey; Schriwer, Geir; Thorisdottir, Audur; Boysen, Preben; Krasnov, Aleksei
Highlights: Responses to vaccination were examined in salmon head kidney during five weeks. Transcriptome analyses showed shift in character of inflammation after two weeks. This coincided with B cells differentiation and increase of nonspecific antibodies. Antibodies to bacterial antigens delivered with vaccine appeared one week later. Antibodies responses were mirrored with changes in repertoire of IgM transcripts. Abstract: The majority of studies of vaccine responses in Atlantic salmon have focused on several weeks after vaccination, and employed a limited number of marker genes. In this study, novel techniques were used to examine a broad panel of expressed genes and antibody repertoire of Atlantic salmon following vaccination. Salmon parr were vaccinated with a multivalent oil-based vaccine, and blood plasma and head kidney were sampled at several time-points between 0–35 days post vaccination. Saline-injected fish were used as control at all time-points. Microarray analyses showed increased expression of immune genes from the first day to the end of study in the head kidney of vaccinated fish. Genes up-regulated in the late phase included several leukocyte markers and components of the oxidative burst complex. A suite of genes that can take part in B cells differentiation were up-regulated from day 14, at which time secretory IgM transcripts also peaked. This coincided with marked increased plasma titres of non-vaccine specific antibodies binding to a hapten-carrier antigen DNP-KLH, while antibodies to bacterial components of the vaccine, Moritella viscosa and Aeromonas salmonicida, first showed significantly elevated antibody levels at day 21, and at a markedly lower magnitude than the non-vaccine specific titres. Sequencing of the variable region of IgM heavy chain (CDR3) revealed higher cumulative frequencies of unique clonotypes in vaccinated salmon starting from day 14 when specific antibodies were first detected. Reduced sequence variance of CDR3 suggested expansion of recently emerged clonotypes. Overall, the results presented here follow a broad panel of gene expression, immunoglobulin sequencing and plasma antibody titres in the first few weeks after vaccination of Atlantic salmon, pointing to a potentially important contribution of non-vaccine specific antibody responses early in the vaccine response.